Psychological readiness is related to return to sport in judo injuries: a cross-sectional study - Lambert, C.; Guenther, D.; Schütz, L.; Kern, N.; Ritzmann, R.; Reinert, N.; Walz, M.; Wafaisade, A.; Nagy, K.; Reuter, S. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The aim of this study is to investigate the influence of a judoka's psychological readiness in relation to his ability to return to sport. At the present time, the relationship between physical and psychological readiness to return to sport has not been adequately elucidated.